Patient's head position-dependent safety analysis of birdcage coil, loop array, and dipole array for applications at 300 MHz in magnetic resonance imaging based on hydrogen nuclei: Simulation study - Eunwoo Lee; Taewoo Nam; Daniel Hernandez; Donghyuk Kim; Yeunchul Ryu; Yeji Han; Kyoung-Nam Kim (Nuclear Engineering and Technology)
The specific absorption rate (SAR) substantially contributes to the elevation of patient temperatures during magnetic resonance imaging (MRI) scans, potentially leading to tissue degeneration and damage. In particular, the relatively short wavelength of radio frequency (RF) used in ultra-high field (UHF)-MRI generates non-uniform RF excitation (|B1+|) and electric (|E|)-fields within the body, with the potential to cause localized increases in tissue temperature. This study employs electromagnetic (EM) simulations to quantitatively assesses variations in SAR resulting from different patient's head positions across three types of RF coils (birdcage coil, loop array coil, and dipole array coil), frequently employed as transmission/reception (Tx/Rx) coils in 7 T MRI. Through analysis of 715 SAR values per RF coil, achieved by varying patient's head positions at 5 mm intervals within the maximum range of movement, the study shows substantial changes in SAR values averaged over 10 g of tissue (SAR10g). Notably, these changes reach a maximum difference of 339.89 % and 371.13 % in comparison to the iso-center (no change), concerning global- and local-SAR10g. Interestingly, the study identifies instances where SAR values surpass the standard SAR limit suggested by the safety guidelines, even when the distance between the RF coil and the patient exceeded 10 mm.